Potential impacts of post-Brexit agricultural policy on fruit and vegetable intake and cardiovascular disease in England: a modelling study. Issue 1 (14th January 2020) - Seferidi, Paraskevi; Laverty, Anthony A; Collins, Brendan; Bandosz, Piotr; Capewell, Simon; O'Flaherty, Martin; Millett, Christopher; Pearson-Stuttard, Jonathan
Abstract : Background: Current proposals for post-Brexit agricultural policy do not explicitly incorporate public health goals. The revised agricultural policy may be an opportunity to improve population health by supporting domestic production and consumption of fruits and vegetables (F&V). This study aims to quantify the potential impacts of a post-Brexit agricultural policy that increases land allocated to F&V on cardiovascular disease (CVD) mortality and inequalities in England, between 2021 to 2030. Methods: We used the previously validated IMPACT Food Policy model and probabilistic sensitivity analysis to translate changes in land allocated to F&V into changes in F&V intake and associated CVD deaths, stratified by age, sex and Index of Multiple Deprivation. The model combined data on F&V agriculture, waste, purchases and intake, CVD mortality projections and appropriate relative risks. We modelled two scenarios, assuming that land allocated to F&V would gradually increase to 10% and 20% of land suitable for F&V production. Results: We found that increasing land use for F&V production to 10% and 20% of suitable land would increase fruit intake by approximately 3.7% (95% uncertainty interval: 1.6% to 8.6%) and 17.4% (9.1% to 36.9%), and vegetable intake by approximately 7.8% (4.2% to 13.7%) and 37% (24.3% to 55.7%), respectively, in 2030. This would prevent or postpone approximately 3890 (1950 to 7080) and 18 010 (9840 to 28 870) CVD deaths between 2021 and 2030, under the first and second scenario, respectively. Both scenarios would reduce inequalities, with 16% of prevented or postponed deaths occurring among the least deprived compared with 22% among the most deprived. Conclusion: Post-Brexit agricultural policy presents an important opportunity to improve dietary intake and associated cardiovascular mortality by supporting domestic production of F&V as part of a comprehensive strategy that intervenes across the supply chain.